The study of national unity in mural art in Perak / Mohamad Quzami An-Nuur Ahmad Radzi - Ahmad Radzi, Mohamad Quzami An-Nuur (2019)
This study has been conducted to investigating the characteristic of national unity mural art in Perak. Mural art has functioned as a fundamental medium and method to represent street art. Consequently, Mural art is more popularly-produced and widespread today compared to previous years. Mural is basically and commonly drawn on the wall surface. Three main objectives are the focus of this study: it’s to determine the characteristics of mural arts in Ipoh, to identify a mural art that represents unity and to analyze the perceptions of audiences towards mural arts that represent unity. The study has been employs qualitative and quantitative method. The qualitative method is focusing on the characteristics of the national unity with the explanations by the expert. The analysis of documentation and visual had support this study too in order to achieve the aims of the research. Researcher has used the Theory of Iconography by Ervin Panofsky and Theory of design by Ovrick to analysis the mural. Therefore the quantitative method is focusing in the perceptions of audiences towards mural arts that represent unity. With the total 200 respondents, a questionnaire survey was conducted involving variety of respondent background. The mean analysis has been conducted to the questionnaire data. It has showed perception of audiences toward chosen mural art in Ipoh, Perak. Although the finding of this paper is focused to mural art in Perak, perhaps the finding could be used in other murals in enhancing national unity in the future.